Geotermisk fjärrvärme i Gunsta - Krouthén, Caroline; Lundgren, Andreas; Mandfloen, Per; Sandberg, Karl-Oskar; Sjöberg-Högerås, Johanna; Thorell, Johan; Wärnsberg Monie, Svante (2014)
Gunsta is situated about 10 km east of Uppsala. Today there are plans to establish 1000 new households in Gunsta before year 2030. The required energy for heating houses and water would be distributed via a district heating system, which also includes 200 existing residences. The annual required energy, according to this study, would be 16.2 GWh with a maximal peak effect of 6.9 MW.